Antibiotic treatment for pyelonephritis in children: multicentre randomised controlled non-inferiority trial. Issue 7616 (4th July 2007) - Montini, Giovanni; Toffolo, Antonella; Zucchetta, Pietro; Dall'Amico, Roberto; Gobber, Daniela; Calderan, Alessandro; Maschio, Francesca; Pavanello, Luigi; Molinari, Pier Paolo; Scorrano, Dante; Zanchetta, Sergio; Cassar, Walburga; et al.
Abstract : Objective To compare the efficacy of oral antibiotic treatment alone with treatment started parenterally and completed orally in children with a first episode of acute pyelonephritis. Design Multicentre, randomised controlled, open labelled, parallel group, non-inferiority trial. Setting 28 paediatric units in north east Italy. Participants 502 children aged 1 month to <7 years with clinical pyelonephritis. Intervention Oral co-amoxiclav (50 mg/kg/day in three doses for 10 days) or parenteral ceftriaxone (50 mg/kg/day in a single parenteral dose) for three days, followed by oral co-amoxiclav (50 mg/kg/day in three divided doses for seven days). Main outcomes measures Primary outcome was the rate of renal scarring. Secondary measures of efficacy were time to defervescence (<37°C), reduction in inflammatory indices, and percentage with sterile urine after 72 hours. An exploratory subgroup analysis was conducted in the children in whom pyelonephritis was confirmed by dimercaptosuccinic acid (DMSA) scintigraphy within 10 days after study entry. Results Intention to treat analysis showed no significant differences between oral (n=244) and parenteral (n=258) treatment, both in the primary outcome (scarring scintigraphy at 12 months 27/197 (13.7%) v 36/203 (17.7%), difference in risk −4%, 95% confidence interval −11.1% to 3.1%) and secondary outcomes (time to defervescence 36.9 hours (SD 19.7) v 34.3 hours (SD 20), mean difference 2.6 (−0.9 to 6.0); white cell count 9.8×10 9 /l (SD 3.5) v 9.5×10 9 /l (SD 3.1), mean difference 0.3 (−0.3 to 0.9); percentage with sterile urine 185/186 v 203/204, risk difference −0.05% (−1.5% to 1.4%)). Similar results were found in the subgroup of 278 children with confirmed acute pyelonephritis on scintigraphy at study entry. Conclusions Treatment with oral antibiotics is as effective as parenteral then oral treatment in the management of the first episode of clinical pyelonephritis in children. Trial registration Clinical Trials NCT00161330 .